SISTEM MONITORING KUALITAS AIR PADA KOLAM IKAN NILA BERBASIS ARDUINO UNO - Kelvin Setyawan; Hagi Vander Khan, Yogi Muhammad Ilham, Paduloh (ADISAM PUBLISHER, 2026)
The increasing importance of automation in aquaculture has led to the development of an Arduino Uno-based automated water quality control system for tilapia fish ponds. This research aims to monitor and maintain essential water quality parameters, including pH levels, dissolved oxygen (DO), and Total Dissolved Solids (TDS), which are critical for the optimal growth of tilapia. The system utilizes TDS sensors, Arduino Uno microcontrollers, NodeMCU for data processing, and LCD monitors for real-time data display. The findings indicate that this system effectively identifies water quality issues, such as high ammonia levels or unstable pH, thereby facilitating timely interventions. By addressing water quality challenges, the system supports sustainable fish farming practices and enhances the productivity of tilapia aquaculture